2023
DOI: 10.1038/s41467-023-39651-7
|View full text |Cite|
|
Sign up to set email alerts
|

The role and risks of selective adaptation in extreme coral habitats

Abstract: The alarming rate of climate change demands new management strategies to protect coral reefs. Environments such as mangrove lagoons, characterized by extreme variations in multiple abiotic factors, are viewed as potential sources of stress-tolerant corals for strategies such as assisted evolution and coral propagation. However, biological trade-offs for adaptation to such extremes are poorly known. Here, we investigate the reef-building coral Porites lutea thriving in both mangrove and reef sites and show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…One important question remaining is whether there are tradeoffs to the increased thermal tolerance in lineages of massive Porites. For example, colonies of massive Porites from extreme mangrove habitat had lower gene expression variation, reduced skeletal density, and increased porosity compared to populations on "classic" reefs (Scucchia et al, 2023). In Palau, Rivera et al, (2022) found that L3 had lower skeletal density, calcification, and extension rates than the other lineages.…”
Section: Response Variation Among Holobiont Lineages To Thermal Chall...mentioning
confidence: 99%
“…One important question remaining is whether there are tradeoffs to the increased thermal tolerance in lineages of massive Porites. For example, colonies of massive Porites from extreme mangrove habitat had lower gene expression variation, reduced skeletal density, and increased porosity compared to populations on "classic" reefs (Scucchia et al, 2023). In Palau, Rivera et al, (2022) found that L3 had lower skeletal density, calcification, and extension rates than the other lineages.…”
Section: Response Variation Among Holobiont Lineages To Thermal Chall...mentioning
confidence: 99%
“…This severe bleaching event was the first to be recorded after 2016, when a mass coral bleaching event impacted entire reefs in New Caledonia [ 40 ], while only a mild paling of corals was observed in Bouraké (Rodolfo-Metalpa, in situ observations). There is increasing work being undertaken to reveal diverse strategies undertaken by these corals to survive under chronic disturbances [ 20 , 33 , 38 , 41 , 42 ], yet what intraspecific stress-induced physiological response of extreme corals (i.e., corals that live at the edge of their environmental limits [ 43 , 44 ], occur during a stress event remains entirely unexplored.…”
Section: Introductionmentioning
confidence: 99%